The Influence of Economic Openness on Income Inequality Among Provinces in Indonesia - Meikanur Sidiq; Toto Gunarto; Arivina Ratih; Neli Aida; Dedy Yuliawan (Green Publisher Indonesia, 2024)
Economic growth is a macro indicator to measure the success of development, so all countries strive to achieve high economic growth to create prosperity for the society, especially for developing countries. At the beginning of economic growth, income inequality will increase, but over time, income inequality will decrease. This research was conducted to analyze the influence of economic growth rate, non-oil export ratio, non-oil import ratio, and foreign direct investment ratio on income inequality among provinces in Indonesia. The data used in this study is panel data obtained from the Central Statistics Agency covering 34 provinces in Indonesia from 2018 to 2022. The results of this study indicate that the economic growth rate has a positive but not significant effect on income inequality in Indonesia, the non-oil import ratio has a positive and significant effect on income inequality in Indonesia, the foreign direct investment ratio has a negative but not significant effect on income inequality in Indonesia, while the non-oil export ratio does not have a significant effect on income inequality in Indonesia.